Global Learning for Adaptive Management (GLAM) - DFID (DFID Development Tracker, 2016)
To improve the value for money and impact of development interventions by promoting the use of better monitoring, evaluation and learning st rategies that support development programmes to gather and respond to emergent evidence on the effects of interventions, as well as changes in the development context. The Global Learning for Adpative Managemen t programme will make available technical assistance to DFID, USAID an d partners to develop this ‘adaptive management’ approach, as well as build an evidence base to understand links between the use of adaptive management and more effective, efficient, relevant and sustainable de velopment interventions.